(untitled) (Current Horticulture, 2024)
An experiment was conducted to study the effect of organic manures and micronutrients on growth, yield and quality of brinjal (Solanum melongena L.) var. Pusa Uttam during kharif season 2018 at S.K.N. Agriculture University, Jobner (Jaipur). The application of vermicompost (6.6 t/ha) significantly increased number of branches (3.19, 9.17, 13.36 and 15.35 at 30, 60, 90 and 120 DAT), number of leaves (13.79, 77.32, 187.78 and 219.58 at 30, 60, 90 and 120 DAT), fruit length (8.17 cm), fruit diameter (7.31 cm), number of fruits/plant (6.59), fruit weight (129.67 g), fruit yield per plot (17.13 kg /plot) and fruit yield (317.20 q /ha) but days required to 50 per cent flowering was non-significants. The Zn @ 0.5% significantly increased number of branches (3.24, 9.27, 13.50 and 15.49, respectively), number of leaves (14.03, 78.41, 191.51 and 222.49, respectively) fruit length (8.30 cm), fruit diameter (7.41 cm), number of fruit/plant (6.63), fruit weight (131.05 g), fruit yield/plot (17.39 kg /plot) and fruit yield (321.99 q/ha) but days required to 50 per cent flowering was non-significant.